Enhanced degradation of phthalate esters (PAEs) by biochar-sodium alginate immobilised Rhodococcus sp. KLW-1 - Kou, Liangwei (Environmental technology, 2024)
In this study, a new strain of bacteria, named Rhodococcus sp. KLW-1, was isolated from farmland soil contaminated by plastic mulch for more than 30 years. To improve the application performance of free bacteria and find more ways to use waste biochar, KLW-1 was immobilised on waste biochar by sodium alginate embedding method to prepare immobilised pellet. Response Surface Method (RSM) predicted that under optimal conditions (3% sodium alginate, 2% biochar and 4% CaCl2), di (2-ethylhexyl) phthalate (DEHP) degradation efficiency of 90.48% can be achieved. Under the adverse environmental conditions of pH 5 and 9, immobilisation increased the degradation efficiency of 100 mg/L DEHP by 16.42% and 11.48% respectively, and under the high-stress condition of 500 mg/L DEHP concentration, immobilisation increased the degradation efficiency from 71.52% to 91.56%, making the immobilised pellets have strong stability and impact load resistance to environmental stress. In addition, immobilisation also enhanced the degradation efficiency of several phthalate esters (PAEs) widely existing in the environment. After four cycles of utilisation, the immobilised particles maintained stable degradation efficiency for different PAEs. Therefore, immobilised pellets have great application potential for the remediation of the actual environment